Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Requirements for two-source entanglement concentration - Vidrighin, Mihai; Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Barbieri, Marco; Kolthammer, W. Steven; Datta, Animesh; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)

Evolving fuzzy pattern trees for binary classification on data streams - Shaker, A.; Senge, R.; Hüllermeier, Eyke (Information Sciences)

"Ihr betet an, was ihr nicht kennt" (Jo 4, 22) - Eine neue Sicht auf die Trinität - Krimphove, Dieter

Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen - Krimphove, Dieter; Kruse, Oliver

Europarecht inklusive CD-ROM mit Gesetzen, Urteilen, Hörfassung und interaktiven Falllösungen - Krimphove, Dieter

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients: Implemented Into the Simulator D3FACT - Renken, Hendrik; Brandt, Sascha; Eichert, Felix A.; Klaas, Alexander (Volume 2: 32nd Computers and Information in Engineering Conference, Parts A and B)
Today’s simulation software normally has fixed, built-in editing and visualization views adapted to a specific problem domain. Often this monolithic concept prevents collaborative editing altogether. Even with more flexible concepts, editing simulation models with a heterogeneous set of clients is not possible. In this article we describe a flexible concept for collaborative editing of simulation models with heterogeneous clients, such as web-based, desktop and mobile clients. The clients may even show different editing views adapted to the user’s role. The concept we describe in this paper overcomes several problems: First we need to be able to connect and manage a set of heterogeneous clients in the simulation software. The very different user inputs from the connected clients then need to be processed, interpreted and combined to allow editing in a collaborative way for all users. At last we show a prototypical integration of the presented concept into our research platform d3fact.

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Multi Reflection of Lamb Wave Emission in an Acoustic Waveguide Sensor - Schmitt, Martin; Olfert, Sergei; Rautenberg, Jens; Lindner, Gerhard; Henning, Bernd; Reindl, Leonhard (Sensors)

Detection of coatings within liquid-filled tubes and containers by mode conversion of leaky Lamb waves - Schmitt, M.; Schmidt, K.; Olfert, S.; Rautenberg, J.; Lindner, G.; Henning, Bernd; Reindl, L. M. (Journal of Sensors and Sensor Systems)
Abstract. In this paper, a new acoustic sensor principle for coating detection within liquid-filled tubes and containers based on mode conversion of leaky Lamb waves is introduced. Leaky Lamb waves are excited and detected by single-phase transducers, which are attached on the outer side of a tube or container. By transmission time and amplitude measurements, coating formation within the liquid-filled tube and container is detected non-invasively. This new sensor principle is subdivided into the separate considerations of Lamb wave excitation, mode conversion and inverse mode conversion. The Lamb wave excitation by a single-phase transducer is visualized by scanning laser Doppler vibrometer imaging. The mode conversion process of leaky Lamb waves is measured by membrane hydrophone measurements and Schlieren visualization; afterwards, the measured emission angles are compared with the theoretical one. The inverse mode conversion process of pressure waves back to leaky Lamb waves is visualized by Schlieren images. By merging the results of Lamb wave excitation, mode conversion and inverse mode conversion, the new sensor concept is explained. Theoretical considerations and measurement results of adhesive tape coating inside a liquid-filled plastic tube and a liquid-filled stainless steel container verify the new acoustic sensor principle. Finally the measuring sensitivity and the technical realization are discussed.

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd (tm - Technisches Messen)

B5.4 - Signal Processing for Single Transducer Distance Measurement Applications to Reduce the Blind Zone - Schröder, A.; Henning, Bernd

Utilizing ultrasound material parameter determination for the characterization of different stages of ageing in Polyamide 6 - Bause, Fabian; Budde, Christopher; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar
The condensation polymer Polyamide 6 (PA 6) is a thermoplastic resin with high tensile strength and rigidity at comparatively low costs for raw material and processing. This is why PA 6 is a common material for the production of ropes, gears or bearings. Apart from that, a relative new application is the thermoforming of glass fibre laminate sheets with PA 6 as matrix material. The prediction the rest of life period of such high-tech materials is still a research objective. A first step, and also part of this contribution, is the nondestructive investigation of the matrix material. The ageing of PA 6 is mainly affected by thermo- and photo-oxidation as well as post-condensation, which e.g. results in a change of physical properties. For this contribution the acoustical and mechanical material parameters of artificially aged PA 6 have been determined with high frequency ultrasound (1 MHz) and quasi-static experiments. We will give a short description of both experimental setups as well as the ageing procedure. Finally we will discuss the correlation between the experimental results, finding that there is a good correlation between sound velocity and tensile strength.

Ultrasonic Waveguide Signal Decomposition Using the Synchrosqueezed Wavelet Transform for Modal Group Delay Computation - Bause, Fabian; Huang, Boqiang; Kunoth, Angela; Henning, Bernd
Due to the modal behavior of geometrically bounded media, ultrasonic guided waves propagate in waveguides as a combination of multiple dispersive wave packets, which can be simulated as a PDE-problem. Given an excitation in time and space, multiple eigen-modes derived from solving the PDE may propagate each with different dispersion characteristics and weight. Considering a broad-band pulse exciting from one side of a hollow cylindrical waveguide, the received signal at the other side consists of all propagating eigen-modes that can be considered approximately as the narrow band signals. The synchrosqueezed wavelet transform (SWT) is employed to sharpen the time-frequency representation (TFR) of the received waveguide signal. Using a ridge detection algorithm, we successively separate the synchrosqueezed TFR into several narrow band TFRs which can be identified as oscillatory components with time-varying frequency. Then those separated TFRs are reconstructed as narrow band signals using the inverse SWT. Based on an analytical model of the waveguide, we observe that the decomposed signals are similar to those dominant eigen-modes simulated above. Moreover, also the group delay and, therefore, the group velocity of each decomposed signal can be estimated well. This is of high interest when analyzing the characteristic of a given waveguide, such as acoustical property measurements or non-destructive testing.

Utilizing interval-Newton approach for the reliable computation of roots in analytical waveguide modeling - Bause, Fabian; Unverzagt, Carsten; Walther, Andrea; Henning, Bernd

Reliable Computation of Roots in Analytical Waveguide Modeling Using an Interval-Newton Approach and Algorithmic Differentiation - Bause, Fabian; Walther, Andrea; Rautenberg, Jens; Henning, Bernd (Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Modellgestützte NIR-Materialfeuchtemessung mittels Multidetektoranordnung - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd (Technisches Messen)
Zur berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung genutzt. Diese nichtinvasive und schnelle Methode ist geeignet sowohl zur Bestimmung der Feuchte von Schüttgütern als auch zur Charakterisierung von Trocknungsprozessen von Lacken. Die reflektierte Strahlung ist dabei abhängig von Absorption und Streuung in der Beschichtung sowie von den temporären und lokalen Reflexionseigenschaften des Messobjektes. ln dieser Untersuchung ist ein experimenteller Aufbau zur simultanen Messung der gerichteten und der diffus reflektierten Strahlungsanteile realisiert.

Untersuchung zum Trocknungsverhalten poröser Materialien durch NIR-Reflexionsmessungen - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd

A modified electrode topology with increased sensitivity of electrical impedance to piezoelectic material parameters - Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Improved Signal Processing for an Ultrasonic Distance Sensor with Reduced Blind Zone - Schröder, Andreas; Henning, Bernd (Proceedings of the International Conference on Acoustics)
Single transducer distance sensors have a blind zone because normally the electrical received signal cannot be detected during transmitting. There are several approaches to realize a simultaneous transmit and receive operation. Digital signal processing is the best solution for narrow band systems (air ultrasound transducer) especially when the transmitted signal is coded. Thereby a mathematical model is used to estimate the electrical received signal. A drawback of the digital signal processing is the required computing time to estimate the model and the time of flight of an echo. In this contribution the computing time is reduced significantly by using base band signals for the signal processing. The signal-processing is subdivided into the following steps: Preprocessing, model identification, estimation of the received signal and echo detection. Beside the model identification the signal-preprocessing is an important part of the system. It depends on the time of flight of an echo (close echo, far echo) and the state of the system (single measurement, averaging). The whole system is evaluated with measurements using a 40 kHz air ultrasound transducer in front of a reflector with varying distances between 0 mm and 1000 mm.

Modified electrode shape for the improved determination of piezoelectric material parameters - Unverzagt, Carsten; Rautenberg, Jens; Henning, Bernd; Kulshreshtha, Kshitij (Proceedings of the 2013 International Congress on Ultrasonics)

A Comparison of Alternative Ways to Identify Singular Matrices - Walther, Andrea; Bause, Fabian; Henning, Bernd

Adaptive Test and Diagnosis of Intermittent Faults - Cook, Alejandro; Rodriguez Gomez, Laura; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Learning to rank lexical substitutions - Szarvas, G.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings EMNLP-2013 Conference on Empirical Methods in Natural Language Processing, Seattle, USA)

Optimizing the F-measure in multi-label classification: Plug-in rule approach versus structured loss minimization - Dembczynski, K.; Jachnik, A.; Kotlowski, W.; Waegeman, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Top-k selection based on adaptive sampling of noisy preferences - Busa-Fekete, Robert; Szoreny, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Preference-based CBR: General ideas and basic principles - Hüllermeier, Eyke; Cheng, W. (in Proceedings IJCAI-13, 23rd international Joint Conference on Artificial Intelligence, Beijing, China)

Rule chains for visualizing evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

Recovery analysis for adaptive learning from non-stationary data streams - Shaker, Ammar; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

BlogForever: From web archiving to blog archiving - Kalb, Hendrik; Lazaridou, Paraskevi; Banos, Vangelis; Kasioumis, Nikos; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Establishing interoperability of a blog archive through linked open data - Kalb, Hendrik; Lazaridou, Paraskevi; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Influence and Dissemination Of Sentiments in Social Network Communication Patterns - Hillmann, Robert; Trier, Matthias (ECIS 2013 Proceedings)
Previous research suggests the existence of sentiments in online social networks. In comparison to real life human interaction, in which sentiments have been shown to have an influence on human behaviour, it is not yet completely understood which mechanisms explain how sentiments influence users in online environments. We develop a theoretical framework that tries to bridge the gap between social influence theories that focus on offline interactions on one hand and online interaction in social networks on the other hand. We then test our hypothesis about the influence and dissemination of sentiments in a quantitative analysis that is based on retrieved textual messages of communication patterns in over 12000 online social networks. Our empirical results suggest a general influence of sentiments on node communication patterns that is evidenced by increased occurrences of subsequent messages that express the same sentiment polarization. We interpret these findings and suggest future research to advance our currently limited theories that assume perceived and generalized social influence to path-dependent social influence models that consider actual behaviour.
Keywords: Social Network Analysis; Sentiment Analysis; Communication Patterns

Interoperability of Web Archives and Digital Libraries: A Delphi Study - Kalb, Hendrik; Lazaridou, Paraskevi; Pinsent, Edward; Trier, Matthias (Proceedings of the 10th International Conference on Preservation of Digital Objects)
The interoperability of web archives and digital libraries is crucial to avoid silos of preserved data and content. While various researches focus on specfic facets of the challenge to interoperate, there is a lack of empirical work about the overall situation of actual challenges. We conduct a Delphi study to survey and reveal the insights of experts in the field. Results of our study are presented in this paper to enhance further research and development efforts for interoperability.
Keywords: Interoperability; Web Archives; Digital Libraries; Delphi Study

Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

"I Can Simply…"? Theorizing Simplicity as a Design Principle and Usage Factor - Trier, Matthias; Richter, Alexander
The usage of social software to support collaboration and knowledge management in corporate intranets is a pervasive topic in practice and research. However, there remain many open research questions concerning its socio-technical system design. To address this gap and to contribute to a deeper understanding of the role and success of corporate social software, we first identify and conceptualize simplicity as an influential design principle and usage factor. We propose a theoretical framework that helps us to empirically study the role of simplicity based on six case vignettes of corporate social software implementation and use. From the theoretical basis and the empirical analysis we develop a series of theoretical propositions and discuss implications for IS design and adoption.

Förderung medienpädagogischer Kompetenz angehender Lehrerinnen und Lehrer in der ersten Phase der Lehrerbildung - Klar, Tilman-Mathies

Countering Wrapping Attack on XML Signature in SOAP Message for Cloud Computing - Razzaghi Kouchaksaraei, Hadi; Chefranov, Alexander G. (International Journal of Computer Science and Information Security)
It is known that the exchange of information between web applications is done by means of the SOAP protocol. Securing this protocol is obviously a vital issue for any computer network. However, when it comes to cloud computing systems, the sensitivity of this issue rises, as the clients of system, release their data to the cloud. XML signature is employed to secure SOAP messages. However, there are also some weak points that have been identified, named as XML signature wrapping attacks, which have been categorized into four major groups; Simple Ancestry Context Attack, Optional element context attacks, Sibling Value Context Attack, Sibling Order Context. In this paper, two existing methods, for referencing the signed part of SOAP Message, named as ID referencing and XPath method, are analyzed and examined. In addition, a new method is proposed and tested, to secure the SOAP message. In the new method, the XML any signature wrapping attack is prevented by employing the concept of XML digital signature on the SOAP message. The results of conducted experiments show that the proposed method is approximately three times faster than the XPath method and even a little faster than ID.

Geometrical and optical benchmarking of copper guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory† - Jesser, Anton; Rohrmüller, Martin; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Friggeet al.Reply: - Frigge, T.; Wall, S.; Krenzer, B.; Wippermann, St.; Sanna, S.; Klasing, F.; Hanisch-Blicharski, A.; Kammler, M.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Charge compensation by long-period reconstruction in strongly polar lithium niobate surfaces - Sanna, S.; Rode, S.; Hölscher, R.; Klassen, S.; Marutschke, C.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Adsorption of PTCDA on NaCl(100) and KCl(100) - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Monolayer Doping via Phosphonic Acid Grafting on Silicon: Microscopic Insight from Infrared Spectroscopy and Density Functional Theory Calculations - Longo, Roberto C.; Cho, Kyeongjae; Schmidt, Wolf Gero; Chabal, Yves J.; Thissen, Peter (Advanced Functional Materials)

Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

On Semeai Detection in Monte-Carlo Go. - Graf, Tobias; Schäfers, Lars; Platzner, Marco (Proceedings of the International Conference on Computers and Games (CG))

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Laemmle, Benjamin; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Weigel, Robert; Koelpin, Alexander; Kissinger, Dietmar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz f T SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm 2 . The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P 1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P 1dB of -17 dBm.

Integrator and digitizer for a non-coherent IR-UWB receiver - Digel, Johannes; Masini, Michelangelo; Grözing, Markus; Berroth, Manfred; Fischer, Gunter; Olonbayar, Sonom; Gustat, Hans; Scheytt, Christoph (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Impulse-radio ultra-wideband systems (IR-UWB) provide short-range wireless communication and precise localization simultaneously. Especially non-coherent IR-UWB reduces the system complexity which enables the design of low-power receivers. This paper presents an integrating digitizer which integrates rectified baseband pulses of an IR-UWB signal and provides the digitized data to the digital baseband of the receiver. The integrator is composed of two time-interleaved (TI) operational amplifiers with capacitive feedback. With this structure, the integrator can be periodically reset without introducing a dead time between two integration periods. The analog-to-digital conversion is performed by a 6 bit 62.4 MS/s successive approximation register analog-to-digital converter (SAR ADC). The integrating digitizer chip is realized in a 250 nm SiGe:C BiCMOS technology from IHP.

A low-cost miniature 120GHz SiP FMCW/CW radar sensor with software linearization - Sun, Yaoming; Marinkovic, Miroslav; Fischer, Gunter; Winkler, Wolfgang; Debski, Wojciech; Beer, Stefan; Zwick, Thomas; Girma, Mekdes Gebresilassie; Hasch, Jürgen; Scheytt, Christoph (Solid-State Circuits Conference Digest of Technical Papers (ISSCC), 2013 IEEE International)
This paper presents an integrated mixed-signal 120GHz FMCW/CW radar chipset in a 0.13μm SiGe BiCMOS technology. It features on-chip MMW built-in-self-test (BIST) circuits, a harmonic transceiver, software linearization (SWL) circuits and a digital interface. This chipset has been tested in a low-cost package, where the antennas are integrated. Above 100GHz, our transceiver has achieved state-ofthe-art integration level and receiver linearity, and DC power consumption.

Towards mm-wave System-On-Chip with integrated antennas for low-cost 122 and 245 GHz radar sensors - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Complex integrated 122 and 245 GHz SiGe BiCMOS transceiver ICs as well as an efficient broadband on-chip antenna are presented. The ICs target radar and sensing applications for the ISM bands at 122 and 245 GHz. Due to high level of integration and basic mm-wave self-testing production as well as test cost are dramatically reduced. Furthermore a compact and efficient on-chip antenna allows for chip-on-board mounting without RF interfaces.

49 GHz 6-bit programmable divider in SiGe BiCMOS - Ergintav, Arzu; Sun, Yaoming; Scheytt, Christoph; Gürbüz, Yasar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
In this paper, a 6-bit true modular programmable frequency divider with division ratios ranging from 64 to 127 is reported. It is composed of a divider chain of 6 divide-by-2/3 cells, and ECL stages that are introduced as synchronization circuits for programming inputs. The synchronization circuits have CMOS input for compatibility with programming circuits. The stand-alone divider chain is functional up to an input clock frequency of 49 GHz. The combination of the divider chain with synchronization circuits is functional up to 44 GHz. The 6 stage divider draws 34 mA current from a 2.7 V supply. The synchronization circuits draw 30 mA from a 3 V supply. The circuit is fabricated in a 0.13 μm SiGe BiCMOS technology, and is well suited for millimeter-wave phase-locked loop (PLL) circuits which require fine frequency resolution.

245 GHz subharmonic receivers in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium)
Two subharmonic receivers for 245 GHz spectroscopy sensor applications in the 245 GHz ISM band have been proposed. One receiver consists of an 2nd APDP (antiparallel diode pair) passive SHM (subharmonic mixer), a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA (power amplifier). The other consists of a single-ended four-stage CB (common base) LNA, an 2 nd APDP passive SHM, an IF amplifier, a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA. The receivers are fabricated in a SiGe:C BiCMOS technology with f T /f max =300/500 GHz. The measured conversion gain are -17 dB rsp. 10.6 dB at 245 GHz with 3-dB bandwidths of 13 GHz rsp. 14 GHz, and the single-side band noise figure are 17 dB rsp. 20 dB; the two receivers dissipates a power of 213 mW and 312 mW, respectively.

A 240 GHz Direct Conversion IQ Receiver in 0.13 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium,)
A 240 GHz direct conversion IQ receiver manufactured in 0.13 SiGe BiCMOS technology with f T /f max of 300/500 GHz is presented. The receiver consists of a four stage LNA, an active power divider, an LO IQ generation network, and direct down-conversion fundamental mixers. The integrated IQ receiver yields a conversion gain of 18 dB, an 18 dB simulated DSB NF, and a 3 dB bandwidth of 25 GHz. The required 245 GHz LO power is in the order of -10 dBm. The receiver exhibits an IQ amplitude and phase imbalance of 1 dB and 3° respectively. It draws 135 mA from the 3.5 V supply and 20 mA from 2 V.

245 GHz Subharmonic Receiver in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Meliani, Chafik (IEEE International Microwave Symposium, Advances in Low Noise Amplifiers and Receivers)
A subharmonic receiver for 245 GHz spectroscopy sensor applications have been proposed. The receiver consists of a CB (common base) LNA, 2 nd transconductance SHM (subharmonic mixer) and a 120 GHz push-push VCO with 1/64 divider. The receiver is fabricated in f T /f max =300/500 GHz SiGe: C BiCMOS technology. Its measured single-ended gain is 14.3 dB at 245 GHz with tuning range of 15 GHz, and the single-side band noise figure is 19 dB. The input 1-dB compression point is at -24 dBm. The receiver dissipates a power of 200 mW.

Wireless 100Gb/s Using A Powerand - Scheytt, Christoph (IEEE International Conference on Communications)

Hardware-Effizientes Mixed-Signal Entzerrfilter - Scheytt, Christoph

Konzipierung eines selbstoptimierenden hybriden Energiespeichersystems unter besonderer Berücksichtigung der Verlässlichkeit - Gausemeier, Jürgen; Iwanek, Peter; Dorociak, Rafal; Stille, Karl Stephan Christian; Böcker, Joachim (Wissenschaftsforum Intelligente Technische Systeme, 9. Paderborner Workshop Entwurf mechatronischer Systeme)
Die absehbare Entwicklung der Informations- und Kommunikationstechnik wird mechatronische Systeme mit inhärenter Teilintelligenz ermöglichen. Hierfür verwenden wir den Begriff Selbstoptimierung (S.O.). Selbstoptimierende (s.o.) Systeme reagieren autonom und flexibel auf sich ändernde Umfeldbedingungen [ADG+09]. Die Entwicklung derartiger Systeme erfordert eine enge Zusammenarbeit der Entwickler der beteiligten Domänen Mechanik, Elektrik/Elektronik, Regelungstechnik und Softwaretechnik. In diesem Beitrag wird erklärt, wie die Steigerung der Verlässlichkeit durch S.O. bei der Konzipierung eines s.o. Systems adäquat berücksichtigt wird. Die Konzipierung des hybriden Energiespeichersystems des innovativen Schienenfahrzeugs RailCab wird retrospektive durchgeführt. Dies erfolgt von der ersten Funktionsdefinition über die Lösungsauswahl und die dazugehörige Nutzwertanalyse bis hin zur Produktkonzeption des Energiespeichersystems. Es wird gezeigt, wie die Schwachstellen und Widersprüche eines technischen Systems identifiziert sowie mit Hilfe geeigneter Gegenmaßnahmen behoben werden können. Hierbei soll insbesondere die Integration der S.O. als Möglichkeit zur Behebung der Schwachstellen betrachtet werden. Somit wird gezeigt wann und wie die Entscheidung über die s.o. Auslegung des Systems getroffen und die Steigerung der Verlässlichkeit dabei ins Kalkül gezogen wird.
Keywords: Konzipierung; Selbstoptimierung; Verlässlichkeit; Mechatronik; Hybrider Energiespeicher; LEA-Publikation; Eigene

Selbstoptimierung in der Anwendung - Böcker, Joachim; Buchholz, Oleg; Romaus, Christoph; Schulte, Christoph; Stille, Karl Stephan Christian (Wissenschaftsforum Intelligente Technische Systeme, 9. Paderborner Workshop Entwurf mechatronischer Systeme)
Die absehbare Entwicklung der Informations- und Kommunikationstechnik wird mechatronische Systeme mit inhärenter Teilintelligenz ermöglichen. Hierfür verwenden wir den Begriff Selbstoptimierung (S.O.). Selbstoptimierende (s.o.) Systeme reagieren autonom und flexibel auf sich ändernde Umfeldbedingungen [ADG+09]. Die Entwicklung derartiger Systeme erfordert eine enge Zusammenarbeit der Entwickler der beteiligten Domänen Mechanik, Elektrik/Elektronik, Regelungstechnik und Softwaretechnik. In diesem Beitrag wird erklärt, wie die Steigerung der Verlässlichkeit durch S.O. bei der Konzipierung eines s.o. Systems adäquat berücksichtigt wird. Die Konzipierung des hybriden Energiespeichersystems des innovativen Schienenfahrzeugs RailCab wird retrospektive durchgeführt. Dies erfolgt von der ersten Funktionsdefinition über die Lösungsauswahl und die dazugehörige Nutzwertanalyse bis hin zur Produktkonzeption des Energiespeichersystems. Es wird gezeigt, wie die Schwachstellen und Widersprüche eines technischen Systems identifiziert sowie mit Hilfe geeigneter Gegenmaßnahmen behoben werden können. Hierbei soll insbesondere die Integration der S.O. als Möglichkeit zur Behebung der Schwachstellen betrachtet werden. Somit wird gezeigt wann und wie die Entscheidung über die s.o. Auslegung des Systems getroffen und die Steigerung der Verlässlichkeit dabei ins Kalkül gezogen wird.
Keywords: Konzipierung; Selbstoptimierung; Verlässlichkeit; Mechatronik; Hybrider Energiespeicher; LEA-Publikation; Eigene

Crosslinked Test Benches - Stille, Karl Stephan Christian; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)
Keywords: Eigene

Online capable optimized planning of power split in a hybrid energy storage system - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Eurocon 2013)

Self-optimization energy management considering stochastic influences for a hybrid energy storage of an electric road vehicle - Romaus, Christoph; Wimmelbücker, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Contradictions and the Foundation of Logic in German Idealism - Ficara, Elena (La question de la logique dans l’Idéalisme allemande)

Kant e il rapporto dello scetticismo con la filosofia - Ficara, Elena (Akten des XI. Kant Kongresses)

Hegel Within Contemporary Logic - Ficara, Elena (Teoria)

Dialectic and Dialetheism - Ficara, Elena (History and Philosophy of Logic)

Wirkungsgradoptimale Arbeitspunktsteuerung für einen permanenterregten Synchronmotor mit vergrabenen Magneten unter Berücksichtigung von Temperatureinflüssen - Wallscheid, Oliver; Böcker, Joachim (ETG-Fachbericht-Internationaler ETG-Kongress 2013–Energieversorgung auf dem Weg nach 2050)

Discrete-time model of an IPMSM based on variational integrators - Specht, Andreas; Ober-Blöbaum, Sina; Wallscheid, Oliver; Romaus, Christoph; Böcker, Joachim (Electric Machines & Drives Conference (IEMDC), 2013 IEEE International)

The Berlin Group and the Philosophy of Logical Empiricism
Rezensionen: Zbl. Math. 1275.03016 (Leon Harkleroad)

Practice budgets and the patient mix of physicians-Evaluating the effects of remuneration system reforms on physician behaviour in Germany - Schmitz, Hendrik (Journal of Health Economics)

What accounts for the regional differences in the utilisation of hospitals in Germany? - Augurzky, Boris; Kopetsch, Thomas; Schmitz, Hendrik (The European Journal of Health Economics)

Health and the double burden of full-time work and informal care provision—Evidence from administrative data - Schmitz, Hendrik; Stroka, Magdalena A (Labour Economics)

Two-Phase Interleaving Configuration of the LLC Resonant Converter - Analysis and Experimental Evaluation - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Integrated Magnetic for DCM-PSFB Converter - Njiende, Hugues; Li, Rongyuan; Schafmeister, Frank; Ide, Peter

Resonant capacitor clamping circuit in resonant converter - Figge, Heiko; Schafmeister, Frank

Hybrid Energy Storage System (HES) - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)

Design of a high performance ferrite magnet-assisted synchronous reluctance motor for an electric vehicle - Paradkar, Milind; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Fast online model predictive control of IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Co-simulation of an electric traction drive - Schulte, Christoph; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Low Latency Hybrid Hardware-in-the-Loop Simulator for Railway Traction System - Tong, Laisheng; Zou, Huanqing; Sun, Meng; Böcker, Joachim (2013 IEEE Vehicle Power and Propulsion Conference (VPPC))

A Novel LC Resonant Based Partial Booster Scheme for Improved Efficiency and Reduced Cost of Transformerless Photovoltaic Inverters - Krishna, D.V.M.M.; Preckwinkel, H.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Verlustmodellierung und Effizienzoptimierung einer hart schaltenden, netzfreundlichen Pulsgleichrichterstufe (PFC) - Bolte, S.; Baurichter, J.; Henkenius, C.; Fröhleke, N.; Böcker, Joachim; Figge, H. (Internationaler ETG Kongress, Berlin, Germany)

Minimierung niederfrequenter Oberschwingungen in Pulsmustern für 2-Level Umrichter in Antriebssystemen mittels winkelmodulierter Partikel Schwarm Optimierung - Peter, K.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

Formaler Regelungsentwurf für netzfreundliche PFC-Ladegleichrichter unter Anwendung eines Netzbeobachters - Keuck, Lukas; Fröhleke, N.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

High efficiency photovoltaic power conditioning system - Sharabash, H.; Krishna, D.V.M.M.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Can oversampling improve the dynamics of PWM controls? - Böcker, Joachim; Buchholz, O. (2013 IEEE International Conference on Industrial Technology (ICIT))

Comparison of Thyristor-Rectifier with Hybrid Filter and Chopper-Rectifier for High-Power, High-Current Application - Solanki, J.; Krishna, D.V.M.M.; Fröhleke, N.; Wallmeier, P. (PCIM Europe Conference, Nürnberg, Germany)

Dynamical modeling for series-parallel resonant converter under optimized modulation - Cao, Zhiyu; Tao, Junbing; Fröhleke, Norbert; Böcker, Joachim (2013 Twenty-Eighth Annual IEEE Applied Power Electronics Conference and Exposition (APEC))

A simplified mathematical model for DC-balancing and capacitor ripple reduction in 3-level inverters - Krishna, D. V. M. M.; Fröhleke, N.; Böcker, Joachim; Preckwinkel, H. (2013 IEEE International Conference on Industrial Technology (ICIT))

A novel low cost solar central inverters topology with 99.2% efficiency - Preckwinkel, Heiko; Bünte, Andreas; Böcker, Joachim; Fröhleke, Norbert; Dora, Krishna (2013 15th European Conference on Power Electronics and Applications (EPE))

A modular multilevel converter based high-power high-current power supply - Solanki, J.; Fröhleke, N.; Böcker, Joachim; Wallmeier, P. (2013 IEEE International Conference on Industrial Technology (ICIT))